Erectile Dysfunction in Men With Gallbladder Stone Disease: A Nationwide Population-Based Study - Chen, Chien-Hua (Am J Mens Health, 2019)
We assessed the risk of erectile dysfunction after the diagnosis of gallbladder stone disease. We identified 9,362 men aged ≥20 years diagnosed with gallbladder stone disease between 2000 and 2011 from Taiwan’s National Health Insurance Research Database as the study cohort, and we randomly selected 9,362 men from the nongallbladder stone disease population by 1:1 frequency-matching with the case cohort based on age, the index date for the diagnosis of gallbladder stone disease, and comorbidities as the control cohort. All subjects were followed until December 31, 2011, for measuring the erectile dysfunction incidence. The risk of organic erectile dysfunction was higher in the gallbladder stone disease cohort than the nongallbladder stone disease cohort (4.01 vs. 2.69 per 1,000 person-years, adjusted hazard ratio = 1.41, 97.5% confidence interval [1.12, 1.78]), but the risk of psychogenic erectile dysfunction was comparable between the gallbladder stone disease cohort and the nongallbladder stone disease cohort (0.40 vs. 0.28 per 1,000 person-years, adjusted hazard ratio = 1.37, 97.5% confidence interval [0.67, 2.79]). Moreover, gallbladder stone disease men with cholecystectomy exhibited a lower risk of developing organic erectile dysfunction than gallbladder stone disease men without cholecystectomy (adjusted hazard ratio = 0.58, 97.5% confidence interval [0.41, 0.80]). The risk of organic erectile dysfunction contributed by gallbladder stone disease was only significantly higher in men aged ≥65 years (adjusted hazard ratio = 2.21, 97.5% confidence interval [1.34, 3.63]) and in men with comorbidities (adjusted hazard ratio = 1.42, 97.5% confidence interval [1.09, 1.85]). The risk of psychogenic erectile dysfunction contributed by gallbladder stone disease was nonsignificant in each age group and in men with or without comorbidities. Gallbladder stone disease is associated with an increased risk of organic erectile dysfunction, but it has no association with psychogenic erectile dysfunction. History of cholecystectomy for gallbladder stone disease may ameliorate the risk of organic erectile dysfunction; it requires more studies to ascertain the protective mechanism and to clarify whether the existence of gallbladder stone disease is an epiphenomenon or independent risk factor of erectile dysfunction.